Pengaruh Pembelajaran Berbasis Culturally Responsive Teaching terhadap Keterampilan Berpikir Kritis Siswa dalam Mata Pelajaran Pendidikan Pancasila di Kelas IV - ni made yantini; Herlina Herlina; Arif Firmansyah Arif Firmansyah (JURNAL DIKDAS, 2026)
This study aims to determine the effect of the application of Culturally Responsive Teaching (CRT)-based learning on students' critical thinking skills in the Pancasila Education class IV SD Inpres 3 Tondo. This study uses a quantitative approach with a quasi experiment and a nonequivalent control group design. The research sample consisted of 55 students, namely class IV A as a control class with a total of 28 students and class IV B as an experimental class with a total of 27 students. The sampling technique uses purposive sampling.The research instruments were in the form of critical thinking skills tests, observation sheets, and questionnaires. Data analysis techniques include descriptive statistics, normality tests, homogeneity tests, and t-tests. The results of the study show that the application of the Culturally Responsive Teaching learning model has a significant effect on students' critical thinking skills. This is evidenced by the results of the t-test which shows a significance value of 0.000 < 0.05, so that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that learning based on Culturally Responsive Teaching is effective in improving the critical thinking skills of grade IV students in the subject of Pancasila Education at SD Inpres 3 Tondo.Keywords: Culturally Responsive Teaching Model, Critical Thinking, Pancasila Education.